Water quality modeling of oil palm plantation predominated area - a case study - Tang, Jock Kie (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Water quality modeling has always been regarded as a useful t"o ol in water quality management. In this study, Biochemical Oxygen Demand, Dissolved Oxygen, Total Suspended Solids and Total Coliform Counts are simulated along Sg. Telong. The Steady-State condition is considered and First-Order Kinetic Process is assumed for the fate of the above water qualities along Sg. Telong. In this study, Streeter-Phelp Model was used to predict downstream Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS) and Total Coliform Counts (TCC) of Sg. Telong. It was found that the BOD, TSS and TCC levels would drop while DO levels would increase until it reaches DO saturation point downstream from a discharge point upstream. Discharge from other plantations such as Arah Bersama OPP would affect the deoxygenation rate, Kd and the reoxygenation rate, Ka. Therefore, the actual DO levels may deviate from the simulated results as the river flows pass Arah Bersama OPP. This study also looks into the Deoxygenation Rate, Kd, Reaeration Rate, Ka and Settling Coefficient, Ks. With the measured Deoxygenation rate, Kd, Rearation rate, Ka and Settling Coefficient, Ks to simulate the fate of BOD, DO, TSS and TCC at 100m, 200m, 600m, 1km, 2km, 3km, 3.2km, 4km, 5km, 6km, 7km, 8km, 9km, and 9.9km downstream of discharge point. The Deoxygenation rate, " Kd, and Reaeration rate, Ka at 27.3°C were fo~nd to be 0.717 s-', and 0.894 s-', respectively. The observed initial Oxygen deficit was 5.27 mglL at O-km. The measured Oxygen deficit was 5.27 mglL at O-km and decreased to 0.00 mg/L at 9.7 km downstream of discharge point. The TSS levels were simulated in four different ranges for particles with aerodynamic diameters of 50 - 75 11m, 76 - 100 11m, 101 125 11m and 126 - 15Q 11m with Settling Coefficients, Ks at 0.003 s-', 0.005 s-', 0.009 , ii S-I and 0.013 S-I at 27.3°C, respectively. A comparison of the mathematical model simulated and measured water qualities at 3.2 km downstream of discharge point, the simulated results are in good agreement with measured values. To achi~ve effective pollution control, water resource management and sustainable development, quantitative contributions and environmental impacts should be identified and assessed.